Containing revolution: democracy promotion, the Cold War and US national security. Issue 5 (September 2018) - Pee, Robert
Abstract This article examines the rise of democracy promotion as a US national security priority and the origins of the US' first democracy promotion organization: the National Endowment for Democracy. During the 1970s, non-state actors called for the foundation of a private democracy promotion organization to overcome strategic and organizational dilemmas which had resulted in the US state limiting its export of democracy in favour of short-term national security objectives and restraining state–private network organizations during the Cold War. Blueprints for a private democracy foundation resolved these dilemmas by removing the US state as the key actor in democracy promotion. However, the fact that private democracy promoters required state funding to be effective led to a reconciliation with the state, and the foundation of the NED as a privately managed but state-funded organization during the Reagan administration. This reconciliation has led to a recurrence of previous dilemmas, which impact US democracy promotion today.